(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: Medical research has developed remarkably in recent years, including the involvement of the glutathione peroxidase (GPx) family of enzymes in the course of human aging, with numerous clinical studies published in the literature reporting this particularfact. Thus, mud therapy and its effect on biological aging have been represented in papers that have been published to date. Papers published in the literature analyzing GPx vari‐ation during sapropelic mud therapy suggest the beneficial effect of this family of en‐zymes in diseases with an important inflammatory component, mainly monitored in patients with osteoarthritis. This study investigated the effects of sapropelic mud treat‐ ment on GPx values in patients receiving treatment with sapropelic mud at the Balneal and Rehabilitation Sanatorium of Techirghiol, Romania. We included 52 patients, split into two groups, who received treatment with cold mud baths and warm mud baths. Values close to statistical significance were found in patients who received treatment with cold mud baths in terms of mean GPx values at the four‐time points studied. Fur‐ther studies evaluating GPx in patients receiving sapropelic mud treatment are needed. Keywords: glutathione peroxidase (GPx), sapropelic mud, peloidotherapy, balneotherapy